2019
DOI: 10.1111/imb.12617
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference‐mediated knockdown of the transcription factor Krüppel homologue 1 suppresses vitellogenesis in Chilo suppressalis

Abstract: Vitellogenesis in holometabolous insects involves the production and secretion of vitellogenin (Vg) and other yolk protein precursors in developing oocyte by the fat body, all of which is predominantly orchestrated by juvenile hormone (JH). Krüppel homologue 1 (Kr‐h1) is a zinc finger transcription factor that has been demonstrated to be a JH‐early inducible gene and to contribute to reproduction. However, the exact molecular function of Kr‐h1 in insect reproduction is poorly understood. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…The role of Kr-h1 in insect vitellogenesis varies among insect species. In L. migratoria, B. dorsalis, and the rice stem borer Chilo suppressalis, Kr-h1 mediates JH action to promote vitellogenesis and oocyte maturation (Song et al, 2014;Yue et al, 2018;Tang et al, 2020). In Ae.…”
Section: Jh Action On Vg Synthesismentioning
confidence: 99%
“…The role of Kr-h1 in insect vitellogenesis varies among insect species. In L. migratoria, B. dorsalis, and the rice stem borer Chilo suppressalis, Kr-h1 mediates JH action to promote vitellogenesis and oocyte maturation (Song et al, 2014;Yue et al, 2018;Tang et al, 2020). In Ae.…”
Section: Jh Action On Vg Synthesismentioning
confidence: 99%
“…43,49 In previous studies, Kr-h1 has been extensively used in a wide range of hemimetabolous and holometabolous insects. [43][44][45][49][50][51][52][53][54][55][56] It appears to exert antimetamorphic action in these insects which protects them from precocious molting. 44,45,53,54 qRT-PCR data based on previous studies have shown that its expression varies with species and life stage.…”
Section: Discussionmentioning
confidence: 99%
“…It was first identified in Drosophila melanogaster as a homolog to a segmentation gene Krüppel , with homology in the zinc‐finger motifs 43,49 . In previous studies, Kr‐h1 has been extensively used in a wide range of hemimetabolous and holometabolous insects 43–45,49–56 . It appears to exert anti‐metamorphic action in these insects which protects them from precocious molting 44,45,53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in adult insects, JH transduces its signal via Met and Kr-h1. Multiple studies have confirmed the involvement of JH in vitellogenin synthesis in the fat body, lipid accumulation in the primary oocyte, regulation of mating and sex pheromone production in several insects [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Moreover, an effect on the number of eggs deposited could be attributed to JH as well, since a reduced number of eggs laid was observed upon silencing Met or Kr-h1 in the brown planthopper, N. lugens [22].…”
Section: Introductionmentioning
confidence: 96%